Hemodialysis (IntechOpen, 2021)
In this special issue, reviews of various aspects of HD therapy were submitted from both groups. In particular, various methods for vascular access were discussed by many contributors. From these reviews, the reader will gain precious hints and suggestions in every day practice. Previously, many textbooks on "Hemodialysis" have been published but they were written by only a couple of authors. However, in this special issue several authors discussed similar subjects, producing precious and fruitful suggestions. This will be very helpful for readers to understand and carry out HD practice. I hope this special issue will contain useful information for those who are involved in HD therapy.